(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
The article reported that in several mud volcanoes of the Kerch Peninsula found 21 species of moss, that belong to 16 genera, 6 families, 2 avascular higher plants divisions –Marchantiophyta and Bryophyta. Observed substrate preferences of these moss in the studied landscape highlight their timed to floral classes of vegetation. The results of structural analysis of mud volcanoes bryophlora. The article contains an annotated list of species, noting points of collection.